EMOTION IN IRVING KARCHMANR’S NOVEL MASTER OF THE JIN - Dedi Darmadi; Purwarno Purwarno; M. Manugeren (Universitas Islam Sumatera Utara (UISU), 2018)
The research is about the analysis of the emotion of some characters in Karchman’s novel Master of the Jin. The purpose of this research to describe types of emotion shown by the main characters emotions of the character in the novel Sang Raja Jin. Feelings and emotions are generally dubbed as state existing in the individual or organism at a time. For example, a person feels sad, happy, afraid, angry or other symptoms after seeing, hearing, or feeling something. In other words, feelings and emotions are characterized as a psychological state in organisms or individuals as a result of events or circumstances experienced by the organism. (Izard, 1990). This research used qualitative descriptive method and psychology literature approach (Moleong, 2010) The source of data was derived from the novel Sang Raja Jin. The finding shows that both the positive and the negative emotions are found in the novel. The positive emotions are love and happy emotion. Meanwhile, the negative emotions were anxious, fear, anger, sad emotion.